Knowledge, Perception And Practice Of Preventive Lifestyle Against HIV/AIDS Among Students Of A Tertiary Educational Institution In South Eastern Nigeria. - Ngozi Immaculata UGWU; Collins Nwachi UGWU; Chima Ariel ONOKA; Festus Ehigiator IYARE; Alfred Friday UNA (Journal of Clinical Research In HIV AIDS And Prevention, 2015)
HIV/AIDS has become a global scourge affecting mainly young people. Sexual behavior change remains the most effective way of preventing further spread. The aim of this study is to assess the knowledge, perception and practice of safe lifestyles towards prevention of HIV infection among students of a tertiary educational institution in Abakaliki, south eastern, Nigeria. A cross sectional descriptive study was carried out, and participants were selected using multistage sampling technique. Data was collected using a pretested, self administered questionnaire and analyzed using SPSS software, version 20. Three hundred and eighty seven participants were recruited for the study, including 199 (51.4%) males and 188 (48.6%) females. Mean age of participants was 23.6 ±2years. All (100%) of the participants were aware of the existence of HIV/AIDS, with the commonest source of information being electronic media (81.1%). Their knowledge of the routes of transmission and modes of prevention of HIV infection was high, though few of them have some misconceptions. Poor practice of safe lifestyles towards prevention of HIV infection as well as low perception of self-vulnerability to the risk of HIV infection was also found. There was poor practice of preventive lifestyles among the participants despite high knowledge of HIV transmission and preventive measures probably due to low perception of self-vulnerability to the risk of HIV infection. Health education should be intensified to impact sufficient comprehensive knowledge to change low perception of self-vulnerability among the students.
Keywords: HIV/AIDS